2022
DOI: 10.1039/d1cc05908d
|View full text |Cite
|
Sign up to set email alerts
|

The bi-metallic MOF-919 (Fe–Cu) nanozyme capable of bifunctional enzyme-mimicking catalytic activity

Abstract: In this study, we report on a bi-metal organic framework MOF-919 (Fe-Cu) capable of bifunctional-enzyme mimicking activity with oxidase- and peroxidase-like activities. The catalytic activities were examined by using o-phenylenediamine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…As shown in Fig. 2c, the main peaks at 1651 cm À1 , 1449 cm 26 The above results demonstrate the successful synthesis of TiO 2 @-MOF-919(Fe-Cu). The N 2 adsorption-desorption experiments show that TiO 2 @MOF-919(Fe-Cu) is a mesoporous type-IV material with a specic surface area of 406 m 2 g À1 , which is greatly improved compared with the TiO 2 bare spheres (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…As shown in Fig. 2c, the main peaks at 1651 cm À1 , 1449 cm 26 The above results demonstrate the successful synthesis of TiO 2 @-MOF-919(Fe-Cu). The N 2 adsorption-desorption experiments show that TiO 2 @MOF-919(Fe-Cu) is a mesoporous type-IV material with a specic surface area of 406 m 2 g À1 , which is greatly improved compared with the TiO 2 bare spheres (Fig.…”
Section: Resultssupporting
confidence: 64%
“…The diffraction peaks at 2 θ = 2.666°, 3.196°, 3.468°, 4.098°, and 4.657° are consistent with the characteristic diffraction peaks of MOF-919(Fe–Cu) in the literature. 26 The above results demonstrate the successful synthesis of TiO 2 @MOF-919(Fe–Cu). The N 2 adsorption–desorption experiments show that TiO 2 @MOF-919(Fe–Cu) is a mesoporous type-IV material with a specific surface area of 406 m 2 g −1 , which is greatly improved compared with the TiO 2 bare spheres (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Strikingly, FeCo-MOF-H 2 exhibited a higher affinity to H 2 O 2 even when compared with natural HRP as well as reported Fe-based and Co-based nanozymes (Table 1). [41][42][43][44][45][46][47][48][49][50][51] Furthermore, FeCo-MOF-H 2 has a larger ν max than most of those nanozymes. These results also confirmed that the multiple sites of Co and Fe II contribute to the synergistic adsorption and catalysis on MOF-based nanozymes.…”
Section: Steady-state Kinetic Studies Of Nanozymesmentioning
confidence: 97%
“…Copper is a metallic element with high ductility and thermal and electrical conductivity (Peralta 1994 ). Copper is an essential mineral for living organs because it plays a key role in the production of the respiratory enzyme of cytochrome oxidase C (Kulandaivel et al 2022 ; Stern 2010 ). Copper nanoparticles exhibit unique properties such as catalytic, antifungal (Asghar et al 2018 ) and antibacterial activity (Parimaladevi et al 2018 ) that are not found in commercial copper.…”
Section: Introductionmentioning
confidence: 99%